Webinar & Workshop Menguasai Design UI/UX melalui Metode Stitch Prompting - Sheva, Bintang; Rianto, Althaf Syafiq; Rahmadillah, Anggi; Dermawan, Ahmad Faiz; Itqon, Muhammad Zaid; Rosanti, Nurvelly; Sutrisno, Mirza; Ambo, Sitti Nurbaya; Hendra; Adharani, Yana (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The rapid development of Artificial Intelligence (AI) technology has significantly accelerated the paradigm of User Interface/User Experience (UI/UX) design. However, practical literacy and skills among the younger generation regarding the use of AI for design productivity remain limited. This community service activity aims to improve the partners' digital literacy and competencies in modern interface design implementation. The program was conducted through a theoretical webinar and a hands-on workshop utilizing the Google Stitch platform (Stitch Prompting). The activity was held online with 27 participants, including members of the Muhammadiyah Student Association (IPM) of SMA Muhammadiyah 18 Jakarta, IPM SMK Muhammadiyah 9 Jakarta, university students, and the general public. The program's effectiveness was evaluated using a comparative analysis of pre-test and post-test data, along with a Likert-scale satisfaction questionnaire. The evaluation results demonstrated a significant increase in cognitive understanding, with the average post-test score reaching 95.83%. The highest leap of 16.7% was recorded in the textual instruction (prompting) understanding indicator, achieving a 100% mastery level. Furthermore, feedback evaluation showed a highly satisfactory response, where 100% of participants gave positive ratings and recommended future programs. This proves that project-based educational intervention is highly effective in bridging the audience's knowledge gap regarding the adoption of artificial intelligence in digital design.